Familial Mutations and Post-translational Modifications of UCH-L1 in Parkinson's Disease and Neurodegenerative Disorders - C. Lee, Yun-Tzai; D. Hsu, Shang-Te (Current Protein and Peptide Science, 2017)
Parkinson’s disease (PD) is one of the most common progressive neurodegenerative disorders in modern society. The disease involves many genetic risk factors as well as a sporadic pathogenesis that is age- and environment-dependent. Of particular interest is the formation of intra-neural fibrillar aggregates, namely Lewy bodies (LBs), the histological hallmark of PD, which results from aberrant protein homeostasis or misfolding that results in neurotoxicity. A better understanding of the molecular mechanism and composition of these cellular inclusions will help shed light on the progression of misfolding-associated neurodegenerative disorders. Ubiquitin carboxyl-terminal hydrolase L1 (UCH-L1) is found to co-aggregate with α-synuclein (αS), the major component of LBs. Several familial mutations of UCH-L1, namely p.Ile93Met (p.I93M), p.Glu7Ala (p.E7A), and p.Ser18Tyr (p.S18Y), are associated with PD and other neurodegenerative disorders. Here, we review recent progress and recapitulate the impact of PD-associated mutations of UCH-L1 in the context of their biological functions gleaned from biochemical and biophysical studies. Finally, we summarize the effect of these genetic mutations and post-translational modifications on the association of UCHL1 and PD in terms of loss of cellular functions or gain of cellular toxicity.
Keywords: UCH-L1